PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN: Studi Empiris Pada Perusahaan LQ45 Periode 2016-2020 - Sulastiningsih Sulastiningsih; Yoga Pradita; Mahamadaree Waeno (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2023)
One of the purposes of establishing a company apart from making a profit is to increase the value of the company. If a company has a high value, then this is positive information for most shareholders, so they are not reluctant to invest funds in the company. Several factors are thought to affect the value of the company, one of which is Good Corporate Governance (GCG). In this study, what is included in Good Corporate Governance is the Board of Commissioners, Board of Directors, and Audit Committee. The number of samples in this study were LQ45 companies from the 2016-2020 period as many as 41 companies using the Purposive Sampling technique. The research data is in the form of an annual report (financial report). Several data analysis techniques in this study include: classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of data processing in regression analysis using the SPSS program produce the following equation formula: = + . From the above equation, it can be concluded that the variable (Board of Commissioners) has a positive and insignificant effect on (Company Value) so that the hypothesis is accepted. Variable (Board of Directors) has a significant negative effect on Firm Value. While the variable (Audit Committee) has a positive and insignificant effect on firm value. Simultaneous test results (F) conclude that the Board of Commissioners, Board of Directors and Audit Committee simultaneously have a significant effect on firm value. While the value of the R Square coefficient in this study is 44.60%, it means that the ability of Good Corporate Governance consisting of the Board of Commissioners, the Board of Directors and the Audit Committee in explaining the Company Value is not strong enough.